2017
DOI: 10.17235/reed.2017.4322/2016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type 2 diabetes mellitus on Khorana venous thromboembolism risk in colorectal cancer patients

Abstract: Background: Many studies have documented the association between venous thromboembolism (VTE) and colorectal cancer (CRC). The Khorana model is a VTE risk assessment model for predicting cancer-associated thrombosis. Type 2 diabetes (T2DM) has also been reported to increase the risk of VTE.Purpose: The aim of this study was to investigate the influence of T2DM on Khorana VTE risk in CRC patients and to explore the relationship between Khorana VTE category and CRC clinicopathological factors.Methods: This analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies have identified DM as a potential risk factor for the development of thromboembolic events such as DVT and PE [16]. DM is thought to contribute to a prothrombotic state by increasing platelet activation, altering coagulation factors, and impairing fibrinolysis [16][17][18]. In addition, DM is often associated with other cardiovascular risk factors, such as obesity, hypertension, and dyslipidemia, which may further increase the risk of thromboembolic events [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified DM as a potential risk factor for the development of thromboembolic events such as DVT and PE [16]. DM is thought to contribute to a prothrombotic state by increasing platelet activation, altering coagulation factors, and impairing fibrinolysis [16][17][18]. In addition, DM is often associated with other cardiovascular risk factors, such as obesity, hypertension, and dyslipidemia, which may further increase the risk of thromboembolic events [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DM is often associated with other cardiovascular risk factors, such as obesity, hypertension, and dyslipidemia, which may further increase the risk of thromboembolic events [19]. Several studies have shown that individuals with DM are at increased risk of developing thromboembolic events [16][17][18][19]. As a result, clinicians need to exercise caution when administering antiangiogenic agents, especially in patients with DM, and maintain good DM control to prevent the development of thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%